Development and validation of the Mental Health Promotion Scale - KADIOĞLU, HASİBE (WILEY, 2022)
Purpose This study aimed to develop and validate a scale that assesses adults' mental health promotion abilities. Design and Methods This study was conducted in Istanbul from October 2016 to May 2018. Three rounds of the Delphi method were conducted to develop the scale. Findings After the third Delphi round, the experts reached a consensus on 93 scale items. Forty-six items were excluded from the scale based on exploratory factor analysis (EFA) results. In the last EFA of the 47-item scale, a 12-factor construct was found with an eigenvalue >1 that explained 64.3% of total variance. The overall Cronbach's alpha of the scale was .93. Practice Implications This scale can be used to assess adults' mental health promotion abilities.
Keywords: Delphi method; instrument development; mental health promotion; reliability; validity; PERSONAL VALUES